Improvement of pig iron production technology by using the useful properties of the potential of secondary resources of raw materials and fuels - Mishalkin , A. P.; Ivashchenko , V. P.; Yaroshenko , O. V.; Petrenko , V. O.; Chumak, D. D. (Theory and Practice of Metallurgy, 2026)
Abstract. The scientific and technical relevance of the study lies in determining the directions for improving the ways of using the useful properties of secondary resources in order to intensify the blast furnace process, increase its energy efficiency and reduce pollutant emissions. At the same time, economic efficiency is achieved by reducing the cost of purchasing primary raw materials and reducing waste generation, which corresponds to modern concepts of sustainable development on the way to "green" metallurgy. Purpose of the study. Scientific and practical substantiation of directions for improving the technology of pig iron production through the use of useful properties of secondary resources of raw materials and fuels that have a man-made origin. It is aimed at increasing the level of energy efficiency and improving the slag regime of the blast furnace process, reducing the man-made load on the environment of industrially developed regions of Ukraine. To achieve this goal, the following theoretical and practical tasks will be solved in the study: The analysis of the current state of use of secondary resources of mineral raw materials and fuel in blast furnace production in the conditions of world and domestic metallurgical enterprises has been carried out. The physicochemical properties of the most common types of secondary resources (man-made wastes of metallurgical origin: dust, sludge, scale, production of metallurgical lime: fractions from gas cleaning devices and heat treatment products of waste of plant origin, which are sources of pyrocarbon) have been investigated. Further - determination of the spectrum of their probable purpose, impact on the features and indicators of the blast furnace process, as well as justification of rational ways of their preparation and use. Rational shares of substitution of traditional raw materials and fuels with secondary materials in the blast furnace process are substantiated, the use of which will not reduce the quality of pig iron and will not increase the specific consumption of coke. Their influence on physicochemical and heat-gas-dynamic processes, which is reflected in the characteristic zones of the blast furnace, has been studied. The optimal technological schemes and recommendations for the methods of introduction and rational specific consumption of innovative materials based on man-made wastes have been determined, which will ensure the maximum level of use of their useful properties in the material and thermal balances of the blast furnace process. The technological and environmental advantages of introducing into the blast furnace process a monomaterial, the composition, physicochemical features and spectrum of purpose of which are formed by heat treatment of a mixture of man-made industrial waste, are evaluated and their prospects as a substitute for the corresponding part of pulverized coal fuel (PCF) and fluxes are determined. Research methods. When conducting a comprehensive study, the following methods will be used: - analysis and generalization of materials of scientific and technical literature and patent sources, coordination of their results in accordance with modern trends and the best results of the practice of using secondary resources in blast furnace production; - physicochemical methods of analysis chemical, thermogravimetric, to determine the composition, structure, metallurgical value, probable spectrum of purpose and reactivity of secondary resources of materials - substitutes for iron ore raw materials, coke and pulverized coal fuel (PCF); - thermodynamic forecasting and kinetic modeling of the behavior of experimental materials of secondary origin under the conditions of their heat treatment to assess the influence of their properties on the course of physical and chemical processes and transformations to the thermal and gas-dynamic regime of the blast furnace. The expected results of the study should also include: - development of scientifically grounded recommendations for the effective use of useful properties of the initial potentials of secondary resources of raw materials and fuel in blast furnace production; - establishment of quantitative ratios regarding rational levels of substitution of traditional fuel and raw materials with secondary ones, without reducing the productivity of the furnace and the quality of pig iron while reducing the specific consumption of lime and PCF; - development of a method for the implementation of a complex technological scheme for the preparation, heat treatment of experimental mixtures based on components of mineral raw materials and fuel, followed by the use of an innovative product in the conditions of blast furnace production of pig iron; Scientific novelty of the work. For the first time, systematically, on the basis of the results of an analytical and practical study, the energy efficiency of production and use in the blast furnace process of a two-component monomaterial based on dispersed waste from the production of lime and materials – waste of plant origin, obtained by implementing the effect of their pyrolysis under conditions of joint heat treatment of the initial mixture layer, was substantiated, tested on high-temperature models, poured thermal, in an inclined rotary drum-type furnace. For the first time, a resource-efficient and results-efficient approach has been used to assess the efficiency of the use of materials based on secondary resources of metallurgical and plant origin, based on an integrated combination of the results of thermodynamic forecasting, physical modeling and taking into account the provisions of the exergical methodology for assessing the energy efficiency of the objects of study. Methodological bases have been developed for the selection of rational schemes for the introduction of complex materials based on secondary materials into the blast furnace charge and in the air blast flow to stabilize gas-dynamic conditions in the charge layer, intensify recovery processes with a decrease in the specific consumption of coke per ton of liquid pig iron. The regularities of the influence of the composition and dispersion of secondary resources on the gas-dynamic and thermal parameters of blast furnace smelting have been revealed, which makes it possible to increase the accuracy of predicting the furnace course. It has been proved that the use of materials based on secondary resources of mineral raw materials and fuels can provide the effects of increasing the energy efficiency of pig iron production and reducing the environmental burden, which meets the requirements of sustainable development and the concept of "green metallurgy".